Essential Mathcad for engineering, science, and math ISE - Maxfield, Brent; Maxfield, Brent (Amsterdam : Elsevier Science, 2009)
Using the author's considerable experience of applying Mathcad to engineering problems, Essential Mathcad introduces the most powerful functions and features of the software and teaches how to apply these to create comprehensive calculations for any quantitative subject. The simple, step-by-step approach makes this book an ideal Mathcad text for professional engineers as well as engineering, science, and math students. Examples from a variety of fields demonstrate the power and utility of Mathcad's tools, while also demonstrating how other software, such as Excel spreadsheets, can be incorporated effectively.
Introduction -- Variables -- Creating and Editing Mathcad Expressions -- Simple User-Defined Functions -- Units! -- Mathcad Settings -- Customizing Mathcad -- Templates -- Arrays, Vectors, and Matrices -- Selected Mathcad Functions -- Plotting -- Simple Logic Programming -- Introduction to Symbolic Calculations -- Solving Engineering Equations -- Advanced Programming -- Putting It All Together -- Assembling Calculations from Standard Calculation Worksheets -- Importing Files from Other Programs into Mathcad -- Communicating with Other Programs Using Components -- Microsoft Excel Component -- Inputs and Outputs -- Hyperlinks and Tables of Contents.
Includes index.
Keywords: ENGINEERING MATHEMATICS -- DATA PROCESSING